THE STUDY OF POTENTIALITY OF PICRORHIZA KURROA ROOT PROTEINS TO INHIBIT FREE RADICALS AND Î‘-AMYLASE ENZYME - S, Sanjay; Banu, Syeda Hajira; M, Chethankumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: To prevent oxidative damage to cells caused by free radicals that are responsible for many diseases, such as atherosclerosis, diabetes and cancer. Picrorhiza kurroa (Katuki) is an ayurvedic medicinal plant used in the current study to evaluate the effectiveness of its root proteins precipitated at 60% ammonium sulfate, and further dialyzed protein sample was investigated for scavenging free radicals and also inhibiting alphaamylase which helps to control postprandial hyperglycemia. Methods: The present study was done by Anti-oxidant methods 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, hydroxyl scavenging method, nitric oxide (NO) method, total anti-oxidant method , Î±-amylase inhibition and its kinetic studies by DNS method. Results: The protein significantly inhibited DPPH radicals 66.19Â±6.08%, hydroxyl radicals 59.18Â±9.05%, nitric oxide radicals 45.38Â±19.52% and total antioxidants present is 82.91Â±2.81% compared with standard ascorbic acid 93.67Â±3.91%. The protein extract (60%) inhibited rat pancreatic Î±-amylase 41.62Â±22.3% compared with acarbose standard 91.09Â±1.8%. These results provide valuable information that P. kurroa proteins exhibits good antioxidant and anti-diabetic property. Conclusion: Picrorhiza kurroa root proteins (60%) posses potent antioxidant and antidiabetic effects. Kinetic studies showed it is a non competitive inhibition. alpha-amylase inhibitor is a protein which inhibits rat pancreatic alpha-amylase specifically at a optimum temperature 37Â°c, pH 6.9, and time 35'. Keywords: Picrorhiza kurroa, Free radicals, Anti-oxidant, Anti-diabetic, Î±-amylase.